Pemeriksaan Penunjang pada Kelainan Rambut - Tasmil, Adina Miltania; Jusuf, Nelva K. (Cermin Dunia Kedokteran, 2024)
Hair evaluation methods are grouped into three main categories: non-invasive methods (for example: questionnaire, daily hair counts, standardized wash test, 60-s hair count, global photographs, dermoscopy, hair weight, contrasting felt examination, phototrichogram, TrichoScan, and polarizing and surface electron microscopy), semi-invasive methods (for example: trichogram and unit area trichogram), and invasive methods (for example: scalp biopsy). This article explores supporting examinations for the diagnosis of hair disorders.